Design And Implementation Of Promotion Mix On Pecel Lele Pak Eko - Listia Nurjanah; Jason Jerico (ConCEPt - Conference on Community Engagement Project, 2023)
This activity aims to help solve problems with Pecel Lele Pak Eko. The lack of knowledge of business owners about the promotion mix results in a lack of income for business owners. Therefore the authors designed a marketing system in the form of a promotion mix to further introduce this business to a wider range by relying on advertisements through social media and designing promotions to attract customers and potential customers. The writing and practical work activities were carried out by the author from September to December 2022. As for the method used by the author to obtain partner data, by observing and interviewing. Judging from the problems found by the author, there is a completion stage given to the Pecel Lele Pak Eko business owner so that the problem can be resolved. Several promotional mix variables used by the author consist of advertising, direct marketing, and sales promotion. The solutions provided by the author include making banners, electronic posters, advertising on social media, and bundle packages. The result of the implementation of the system that has been designed is the emergence of promotional activities that have not previously been carried out by Pecel Lele Pak Eko and the effect of increasing sales.